A Sexual Dysfunction And Quality Of Life Problems Caused By Perineal Pain Cicatrix In A Woman: A Case Report - Edy Fakhrizal; M. Lingga Primananda (Andalas Obstetrics And Gynecology Journal, 2023)
Introduction: Sexual dysfunction is a complaint that could happened because of disturbance in complex processwhich coordinated by neurology system, vascular and endocrine system.1 One cause of sexual disfunction isdyspareunia which also followed by quality of life problems. Problems of dyspareunia, sexual dysfunction andquality of life can be measure with VAS, FSFI and WHOQOL instruments. VAS, Visual Analogue Scale, is one ofthe pain rating scales used in epidemiologic and clinical research to measure the intensity or frequency of varioussymptoms.2 FSFI, Female Sexual Function Index, is a multidimensional questionnaire that can show female sexualfunction. This questionnaire consists of 6 domains in which sexual desire, sexual arousal, lubrication, orgasm,sexual satisfaction and pain.3,4,5 WHOQOL-BREF, World Health Organization Quality-of-Life Scale, is a qualityof life assessment developed by the WHOQOL Group with fifteen international field centres, simultaneously, inan attempt to develop a quality of life assessment that would be applicated by cross-culturally.Case Report : Patient came with complaint of pain in genital opening and perineum that felt since 5 months ago.Patient also came with complaint of dyspareunia. Patient had history of vaginal delivery which causing her aperineal rupture. For 5 months, patient could not get intercourse and made her desperated and suffered becauseof her husband desire. Patient also felt inferiority and these problems disturbed her daily activity. VAS was 8,FSFI was 3, and WHOQOL was 71. The perinel ruptured was sutured at the moment of delivery, but after 1 weekpatient started to felt pain at her birth canal. It was the first pregnancy, delivery process was without anyproblems, baby born with 2900 gram of birth weight. From gynecology examination, found a cicatrix at 5 o’clockdirection, any other gynecology organs within normal limit. Diagnose was dyspareunia ec perineal cicatrix withsexual dysfunction and quality of life problems, then urogynecologist decided to do surgery